Exploring Multicultural Values in Interfaith Lecturer Cooperation: An Ethnography - Syafii, Imam (Edukasi, 2025)
Indonesia’s rich cultural and religious diversity poses both challenges and opportunities in fostering inclusive academic environments. This ethnographic study aims to explore the construction and enactment of multicultural values within interfaith academic collaboration among lecturers at Universitas Terbuka (UT), Indonesia’s leading open and distance education institution. Utilizing a qualitative ethnographic design, data were gathered through in-depth interviews, participatory observations, and document analysis. The study involved four lecturers representing different religious affiliations: Islam, Hinduism, Christianity, and Buddhism. Thematic analysis identified three core findings: (1) religious differences are navigated through mutual respect, professionalism, and shared pedagogical goals; (2) multicultural values such as tolerance, equity, and inclusivity are embedded in teaching practices and research collaborations; and (3) interfaith dialogue is facilitated through adaptive and dialogical communication strategies. These findings reveal that UT’s interfaith academic practices are grounded in both ethical commitment and institutional support for diversity, contributing to a cohesive and productive academic climate. The study highlights the strategic role of multicultural ethics in enhancing educational quality and institutional resilience. It offers practical insights for higher education policymakers in designing effective frameworks for interfaith engagement and intercultural competence development. Furthermore, this research enriches theoretical discourses on multiculturalism in professional academic settings and suggests directions for future comparative or longitudinal studies to examine interfaith dynamics in broader educational landscapes.